OLES: An instrument for refining the design of e-learning environments - Trinidad, Sue; Pearson, J. (Blackwell Science Ltd, 2005)
Designing and implementing effective e-learning is a complex process, which involves many factors. Lecturers need to constantly consider, evaluate and adjust these factors to provide effective e-learning environments for students. In this paper, we report on the design and development of the Online Learning Environment Survey (OLES), an instrument which can be used to gather and represent data on students' ‘actual’ (experienced) and ‘preferred’ (ideal) learning environments. We describe the use of this instrument in blended learning environments with university classes, illustrating how OLES can be used by educators striving for good practice in the design of effective online learning environments.